Empowering Students through Sports: A Study of HED Tournaments in Government College: https://doi.org/10.5281/zenodo.16892508 - Muhammad Rizwan Nawaz; Faisal Waqas; Momena Maheroo; Aqsa Batool; Dr. Mehwish Manzoor * (Journal of Religion and Society, 2025)
This research explores how sports tournaments organized by the Higher Education Department (HED) contribute to the development of leadership qualities, teamwork abilities, and social skills among male students. Using a survey-based approach, data were gathered from participants engaged in these tournaments to evaluate their views on skill development through sports involvement. The analysis indicates a strong positive correlation between active participation in sports and the improvement of vital life skills. Notably, most respondents acknowledged gains in leadership (75.44%), teamwork (77.76%), and social interaction (66.27%). These outcomes are consistent with prior studies, emphasizing sports as an effective medium for personal development. The study further provides actionable insights for policymakers, educators, and sports organizers to strengthen the role of sports in enhancing students’ competencies. Moreover, it stresses the importance of future investigations into the long-term impacts of sports participation across different student groups. In sum, this work adds to the body of knowledge on the significance of sports in higher education and its potential to nurture essential skills among learners. Keywords: Higher Education Department (HED), Sports Tournaments, Sports Participation, Personal Growth.